2014
DOI: 10.1002/2013jd020987
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-borne and Raman lidar observations of Asian dust and cirrus cloud properties over Tsukuba, Japan

Abstract: The vertical distributions of the microphysical and optical properties of tropospheric aerosols and cirrus cloud were measured using an instrumented balloon and a ground-based Raman lidar over Tsukuba, Japan (36°N, 140°E), during the Asian dust events on 9 and 21 May 2007 to investigate the influence of Asian mineral dust on ice cloud formation in the upper troposphere. The instrumented balloon measured the particle size distribution, ice crystal images, dew/frost point, relative humidity, and temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…In addition, Storelvmo and Herger (2014) demonstrated that the forward modelling simulation with 50 % of mineral dust particles acting as INP to be in good agreement with an observation reported by Cziczo et al (2013). Another airborne observation during an Asian mineral dust event also suggested ice nucleation in cirrus clouds to occur under water subsaturation conditions below 130 % RH ice (Sakai et al, 2014). Previously, empirical descriptions such as Meyers et al (1992, henceforth M92) were derived from the limited field measurements of ice nuclei concentrations measured at −23 • C < T < −7 • C and 102 % < RH ice < 125 % conditions.…”
Section: Introductionsupporting
confidence: 73%
“…In addition, Storelvmo and Herger (2014) demonstrated that the forward modelling simulation with 50 % of mineral dust particles acting as INP to be in good agreement with an observation reported by Cziczo et al (2013). Another airborne observation during an Asian mineral dust event also suggested ice nucleation in cirrus clouds to occur under water subsaturation conditions below 130 % RH ice (Sakai et al, 2014). Previously, empirical descriptions such as Meyers et al (1992, henceforth M92) were derived from the limited field measurements of ice nuclei concentrations measured at −23 • C < T < −7 • C and 102 % < RH ice < 125 % conditions.…”
Section: Introductionsupporting
confidence: 73%
“…The results shown that the dust backscatter-related Angstrom exponents (BAEs) values were in the range of 0.3 to 0.6 (±0.2), which indicated domination of coarse particles in the micron size range. Using an instrumented balloon and a ground-based Raman Lidar over Tsukuba, Japan, the influence of Asian mineral dust on an ice cloud formation in the upper troposphere was investigated, and the results pointed that the predominance of nonspherical particles were in the range of 6 to 12 km [34].…”
Section: Introductionmentioning
confidence: 99%
“…Each year during the northern hemispheric summer months from June to August, large amounts of Saharan mineral dust particles are transported from the African continent towards the Caribbean islands (Moulin et al, 1997). Dust particles are injected into the atmosphere over the Saharan, for example by nocturnal low-level jets or convective activity (Schepanski et al, 2009), and form well-mixed convective aerosol layers from ground level to up to 4-6 km height (Esselborn et al, 2008;Ben-Ami et al, 2009;Ansmann et al, 2011). Easterlies subsequently transport the layers westwards over hot desert surfaces towards the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%